The United Nations Security Council Resolution on Sanctions Towards Individual from the Perspective of International Law - Suri, Jessica Priscilla (Padjadjaran Journal of International Law, 2019)
AbstractThe United Nations (UN) Security Council (SC) holds the primary responsibility to maintain international peace and security. The emergence of international terrorism as a threat to international peace and security encourages the SC to impose sanctions in the form of assets freeze, travel ban and arms embargo towards targeted individuals. However, the implementation of UN targeted sanctions towards individuals has been violating the targeted individual?s human rights to property, rights of movement, rights to privacy, honor and reputation, and also the rights to a fair trial. This article explains the legitimation of the SC Resolutions in imposing sanction towards an individual, and the obligation of UN member states towards the SC resolution that imposes sanctions against its citizen. The article argues that violations of human rights stemming from the implementation of SC Resolutions on sanction towards individuals indicate that the resolutions have been adopted beyond the limits of international law. This condition satisfies the invalidity of such resolutions. In accordance with Article 25 and 103 of the UN Charter, all member states have an obligation to accept, carry on and give priority to the obligation originating from the SC Resolution including to implement the sanction measures towards individuals. Nevertheless, member states must accommodate and harmonize its obligations in respecting, protecting and fulfilling all the individuals? rights who are targeted by the SC along with its obligation to the SC Resolutions.Keywords: Human Rights, Sanction towards Individuals, United Nations Security Council. AbstrakDewan Keamanan Perserikatan Bangsa-Bangsa (DK) memiliki tanggungjawab utama untuk menjaga perdamaian dan keamanan internasional. Munculnya terorisme internasional sebagai ancaman terhadap perdamaian dan keamanan internasional mendorong DK untuk menjatuhkan sanksi berupa pembekuan aset, pelarangan perjalanan serta embargo senjata kepada individu yang ditargetkan. Penerapan penjatuhan sanksi tersebut menimbulkan pelanggaran Hak Asasi Manusia (HAM) yaitu hak terhadap properti, hak kebebasan berpindah, hak atas privasi, kehormatan dan reputasi serta hak atas proses pengadilan yang adil. Artikel ini diawali dengan pembahasan legitimasi resolusi DK yang menjatuhkan sanksi kepada individu, serta memaparkan mengenai kewajiban negara anggota PBB terhadap resolusi DK yang menjatuhkan sanksi kepada warga negaranya. Pelanggaran HAM yang disebabkan oleh penerapan penjatuhan sanksi terhadap individu mengindikasikan bahwa resolusi yang mendasari penjatuhan sanksi tersebut diadopsi dengan melampaui batasan-batasan penjatuhan sanksi DK dan telah kehilangan legitimasinya menurut hukum internasional. Sekalipun negara memiliki kewajiban menerima, melaksanakan dan mengutamakan kewajibannya berdasarkan Resolusi DK yang menjatuhkan sanksi terhadap individu, negara tetap harus mengakomodir dan mengharmonisasikan kewajibannya dalam menghormati, melindungi dan memenuhi HAM individu yang dijatuhkan sanksi saat melaksanakan kewajibannya yang berasal dari Resolusi DK.Kata Kunci: Dewan Keamanan Perserikatan Bangsa-Bangsa, Hak Asasi Manusia, Sanksi terhadap Individu.